Growth hormone therapy in a girl with Turner syndrome – An experience from Bangladesh - Nahar, J.; Zabeen, B.; Islam, N.; Azad, K. (Journal of Diabetes and Endocrinology Association of Nepal, 2022)
Turner syndrome (TS) is the most common sex chromosome abnormality in females. Short stature and hypogonadism are principal signs of TS. Turner syndrome is well-established. There have been studies that have evaluated the benefits of growth hormone in TS with significant benefit in adult height. A 9-year 11 months-old girl who presented to the Paediatric Endocrinologist, with complaint of not growing according to her age. Her growth was noticed to be slow from early age but her parents initially thought it was normal. They however became worried when she was not growing yet to start pubertal development. Her parents eventually took her to this referral hospital for further evaluation and management.